2021
DOI: 10.1111/acps.13384
|View full text |Cite
|
Sign up to set email alerts
|

Does cannabis use in adolescence predict self‐harm or suicide? Results from a Finnish Birth Cohort Study

Abstract: Objective Longitudinal studies examining the association between adolescent cannabis use and self‐harm are rare, heterogeneous and mixed in their conclusions. We study this association utilizing a large general population‐based sample with prospective data. Methods The Northern Finland Birth Cohort 1986 (n = 6582) with linkage to nationwide register data was used to study the association of self‐reported cannabis use at age 15–16 years and self‐harm and suicide death until age 33 (until year 2018), based on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…This is in line with the results of a previous birth cohort study on the same population as this study that found a robust association between adolescent (15–16 years) cannabis use and subsequent self-harm requiring medical attention by the age 32–33 but there was not such association found between adolescent cannabis use and death by suicide. 37 In this study, family structure of other than two parents and mother’s low education level were independent risk factors for overdoses and intentional overdoses, which was expected due the previously demonstrated associations with these family background factors and AUD. 4–7 , 11 , 12 , 14–17 …”
Section: Discussionsupporting
confidence: 60%
“…This is in line with the results of a previous birth cohort study on the same population as this study that found a robust association between adolescent (15–16 years) cannabis use and subsequent self-harm requiring medical attention by the age 32–33 but there was not such association found between adolescent cannabis use and death by suicide. 37 In this study, family structure of other than two parents and mother’s low education level were independent risk factors for overdoses and intentional overdoses, which was expected due the previously demonstrated associations with these family background factors and AUD. 4–7 , 11 , 12 , 14–17 …”
Section: Discussionsupporting
confidence: 60%
“…However, while an independent association between cannabis use and bipolar disorder was not seen due to confounding by other substance use, the data still suggest early cannabis exposure to be an adverse clinical marker for onset of bipolar disorder. Moreover, participants in this cohort who smoked cannabis before age 16 years have been shown to be at increased risk of other adverse mental health outcomes, including psychosis [28] and self‐harm [29]. Therefore, reducing cannabis use in adolescents is an important public health priority.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the homicidal intoxication was the most common manner of death among fatalities involving hashish alone in compared with fatalities involving hashish with other drugs. The relationship has been found between hashish abuse, homicide and suicide in several previously published studies [22][23][24][25]. In the Eastern region of Saudi Arabia, hashish abuse ranked the second illicit drugs among suicidal hanging in the period 2014 to 2019 [26].…”
Section: Discussionmentioning
confidence: 99%